National Issues In The “Aravot” Periodical Of The Reorganised Hunchak Party - Hovhannisyan, Gegham (ՀՀ ԳԱԱ «Գիտություն» հրատ.)
In April 1910, in Constantinople, Misak Suryan, a member of the Reorganised Hunchak Party, founded the weekly newspaper “Aravot” (Morning). From its inception, the newspaper adopted a staunchly oppositional stance, which led to its prohibition by the Young Turk government after only a few issues had been published. The publication of “Aravot” resumed in April 1919, serving as the unofficial mouthpiece of the Reorganised Hunchak Party. Between March and October 1921, it functioned as the Constantinople organ of the party. The newspaper addressed a range of issues, with particular emphasis on the First Republic of Armenia, the Armenian Question at the Paris Peace Conference, the activities of the Armenian delegation, Russo-Armenian and Armenian-Entente relations, as well as the improvement of internal Armenian national affairs.
Keywords: Պատմություն